Development of Cultural Arts Learning in Project Based Learning for Students of Elementary School Department, Faculty of Education and Teacher Training, Nusa Cendana University, Kupang- INDONESIA - Sogen, Yosephina (Indonesian Scientific Publication, 2023)
This study focuses on elementary school teacher training students and their efforts to enhance creativity in teaching arts to children. The main issue addressed is the development of materials in the classroom for teaching arts. The research aims to address this issue by incorporating music, fine art, and dance activities into the classroom to foster creativity in both teaching and learning.The study encompasses creativity in classroom management, subject delivery, teaching approaches, and the use of teaching media. Findings indicate that elementary school teacher training students successfully integrate mathematics concepts with fine arts, particularly through geometric shapes drawing and coloring. These creative teaching methods make elementary school students more active and imaginative. The research employs an action research methodology within a qualitative and descriptive framework, emphasizing practical learning. It reveals that teacher training students utilize diverse teaching media to promote creativity in their lessons, including dance, drawing, and music. They collaborate with elementary school teachers to select appropriate skills to teach young students, thus contributing to arts and culture subject development. Teachers employ creative media such as zigzag texture images for fine arts and musical instruments like Pianika and recorder to enhance the learning experience. This participatory approach encourages students' active engagement and direct practice, ultimately aiding teachers in effective classroom management.In summary, this study demonstrates how elementary school teacher training students creatively incorporate arts and culture into their teaching, using various media and approaches to engage students actively in the learning process.